Germany : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Germany. (IMF Staff Country Reports; Country Report, 2022)
The fallout from the war in Ukraine has hit the German economy before it regained its pre-pandemic GDP level, with effects running through higher energy costs, the possibility of gas shortages and broader supply disruptions, and weaker confidence. Consumer price inflation has spiked above 8 percent, largely because of energy price increases, but inflation pressures are becoming more widespread.